Statics for building construction - Burton, Jack L. (Prentice-Hall, 1999)
Adhering to all ANSI and ASTM standards, this informative book on building construction guides readers through the analytical thought process required to make an informed structural analysis. Written from an architectural structural perspective, it demonstrates real-world applications throughout, and suggests numerous hands-on group projects to bring concepts to life. Requires minimal knowledge of algebra and trigonometry; no calculus. Focuses on five major areas of study - Static Physics, Analysis of Forces of Beams, Structural Design, Structural Wood Design, and Structural Concrete Design. Integrates many word problems and sample exercises throughout, and bases all computations covered on two-dimensional forces for simplification. Highlights variable formats and the "scale method", and explores drafting and detailing tools/criteria for illustrating structural solutions.